Annual banned‐substance review: analytical approaches in human sports drug testing. Issue 1 (January 2017) - Thevis, Mario; Kuuranne, Tiia; Geyer, Hans; Schänzer, Wilhelm
Abstract : There has been an immense amount of visibility of doping issues on the international stage over the past 12 months with the complexity of doping controls reiterated on various occasions. Hence, analytical test methods continuously being updated, expanded, and improved to provide specific, sensitive, and comprehensive test results in line with the World Anti‐Doping Agency's (WADA) 2016 Prohibited List represent one of several critical cornerstones of doping controls. This enterprise necessitates expediting the (combined) exploitation of newly generated information on novel and/or superior target analytes for sports drug testing assays, drug elimination profiles, alternative test matrices, and recent advances in instrumental developments. This paper is a continuation of the series of annual banned‐substance reviews appraising the literature published between October 2015 and September 2016 concerning human sports drug testing in the context of WADA's 2016 Prohibited List. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Detection assays for drugs and methods of sports doping published between 2015 and 2016 are critically reviewed and evaluated in context with the Prohibited List 2016 as established by the World Anti‐Doping Agency.